A population study of chromosome 22q11 deletions in infancy. Issue 4 (1st October 1998) - Goodship, Judith; Cross, Ian; LiLing, Jesse; Wren, Christopher
Abstract : AIMS: To determine the prevalence of submicroscopic deletions within chromosome band 22q11 in infants with significant heart disease and compare this with the prevalence of other chromosomal abnormalities causing significant heart disease. To determine a minimum prevalence of deletions within chromosome band 22q11 in infants in the general population. METHODS: Chromosome analysis was performed on samples from infants born in the former UK Northern Health Region in 1994 and 1995 who either had significant heart disease or who were suspected to have a chromosome band 22q11 deletion following referral to the Northern Genetics Service. Significant heart disease was defined as major structural malformation or cases where invasive investigation or intervention was required in infancy. RESULTS: Chromosome band 22q11 deletions were identified in nine infants in a population of 69 129 livebirths, giving a minimum prevalence of 13 per 100 000 (95% confidence interval 4.5 to 21.5). Six cases had significant heart disease, one of whom died before diagnosis. In the same population there were 53 cases of trisomy 21, 15 of whom had significant heart disease. CONCLUSION: The most common chromosomal cause of significant congenital heart disease remains trisomy 21, while the second most common chromosomal cause is deletion in chromosome band 22q11.